Good health literacy leads to better quality of life and medication adherence among hemodialysis patients - Mailani, Fitri; Febriyana, Indah; Rahman, Dally; Sarfika, Rika; Muliantino, Mulyanti Roberto (Universitas Airlangga, 2024)
Introduction: The research aimed to investigate the correlation between health literacy levels, medication adherence, and quality of life among hemodialysis patients with chronic kidney disease. Methods: The research employed a cross-sectional design. A random sample of 164 hemodialysis patients from two hemodialysis facilities in Padang, Indonesia, was collected between May and June 2023. Inclusion criteria were patients undergoing hemodialysis twice a week and aged over 18 years. Patients who experienced a decrease in consciousness and memory disorders such as dementia were excluded from this study. The questionnaires used to measure variables in this study were the demographic data questionnaire, the HLS-EU-Q16 health literacy questionnaire, the MMAS-8 medication adherence questionnaire, and the KDQOL-36 quality of life questionnaire for chronic kidney disease patients. Results: The high health literacy group (N = 73) exhibited a markedly superior quality of life compared to those in the mid-level (N = 48) and low-level (N = 43) health literacy groups. Multiple regression analysis revealed that, of the three components of health literacy, health promotion has the greatest influence on patients' quality of life, contributing 25.1%, while the aspect of healthcare has the greatest influence on medication adherence, contributing 43.3%. Conclusions: Health literacy is essential in improving medication adherence and the patient's quality of life in a more optimal direction. Healthcare professionals should create plans for tailored and customized health information with the goal of providing patients with the knowledge about critical components they need to manage chronic kidney disease.